Implementasi Metode Sentra dalam Pembelajaran Bahasa Arab di Kelas IV SD Tazkia Global Islamic School - Fidatul Qoimah; Agung Muttaqien; Desky Halim Sudjani (Jurnal Syntax Admiration, 2024)
This research aims to determine the planning, implementation, inhibiting and supporting factors of the central method in learning Arabic, especially maharah istima. The research method used in this research is a descriptive qualitative method. The data collection techniques used in this research are observation, interviews and documentation. The results of this research show that (1) There are 2 central method planning for learning Arabic, namely: Teacher mental preparation, Teacher administration, APE/Learning Tools (2) Implementation of the Arabic language learning process using the central method, there are 3, namely: Opening Activities, Activities core, and final activities. (3) There are 3 factors inhibiting the application of the central method in maharah istima' learning, namely: time effectiveness, lack of teacher creativity and student adjustment. (4) Supporting factors for the application of the central method in maharah istima' learning, there are 5, namely, infrastructure, special teacher training, teacher allowances, student motivation and support from parents, especially in class IV SD Tazkia Global Islamic School.